The impact of trade policy uncertainty shocks on the Euro Area - Arigoni, Filippo (knjige, 2021)
This paper sets up a Bayesian SVAR model on Euro Area data and identifies trade policy uncertainty shocks using a minimum set of sign restrictions. We find that rising trade policy uncertainty adversely affects the real business cycle in the Euro Area mostly in the short term, while it has more persistent effects on the real effective exchange rate and, to a lesser extent, on prices. In line with the recent geo-political events, the evidence suggests an increasing contribution to Euro Area fluctuations towards the end of the sample period. The results are robust to alternative measures of trade policy uncertainty. Furthermore, we show that real industries exhibit heterogeneous responses to trade policy uncertainty shocks.
Keywords: Ekonomska politika; Evropska unija; Negotovost (ekonomija); Trgovina